Metaphors we experiment with in multimodal ethnography. Issue 4 (4th July 2019) - Varvantakis, Christos; Nolas, Sevasti-Melissa
ABSTRACT: In this paper, we argue for a view of analysis as an embodied practice and review others' testimonies of carrying out multimodal ethnography. This review suggests that metaphors are key for communicating what happens to us in the course of the research and our subsequent sense-making practices. We identify four metaphors for communicating data collection and analytic practices: composing, meandering, plundering and time travel . We then turn to our own multimodal fieldwork with children in middle childhood, to think about the experiences and emergent metaphors that shaped our practice on an international study looking at the relationship between childhood and public life. Children's play was instructive in our own formation as multimodal ethnographers. We provide examples of the ways in which children recruited us into their play, the ways in which play taught us about what matters to children, and finally, how we took play into our own analytical practices.